Irpex lacteus, a white rot fungus applicable to water and soil bioremediation - Novotný, C; Erbanová, P; Cajthaml, T; Rothschild, N; Dosoretz, C; Sasek, V (Applied microbiology and biotechnology, 2000)
Growth parameters, ligninolytic enzyme activities and ability to degrade polycyclic aromatic hydrocarbons by the fungus Irpex lacteus were characterized and compared with those of other white rot fungi capable of rapid decolorization of poly R-478 and Remazol Brilliant Blue R dyes. I. lacteus was able to grow on mineral and complex media and efficiently colonized sterile and non-sterile soil by exploratory mycelium growing from a wheat straw inoculum. In shallow stationary cultures growing on high nitrogen mineral medium containing 45 mM ammonium as nitrogen source, the fungus produced lignin peroxidase (LIP), Mn-dependent peroxidase (MnP) and laccase simultaneously, the respective maximal activities of 70, 970 and 36 U/l being attained around day 18. Growing in nitrogen-limited medium (2.4 mM ammonium), no LIP was formed and levels of MnP and laccase decreased significantly. During growth in sterile soil, the fungus synthesized LIP and laccase but not MnP. I. lacteus efficiently removed three- and four-ringed PAHs from liquid media and artificially spiked soil. The variety of ligninolytic enzymes, robust growth, capability of soil colonization and resistance to inhibitory action of soil bacteria make I. lacteus a suitable fungal organism for use in bioremediation.
Keywords: Laccase; Biodegradation, Environmental; biodegradace; Culture Media; Soil Pollutants; Water Pollutants, Chemical; látky znečišťující půdu; Basidiomycota; chemické látky znečišťující vodu; peroxidasy; Peroxidases; polycyklické aromatické uhlovodíky; Oxidoreductases; kultivační média; Polycyclic Aromatic Hydrocarbons; lakasa; oxidoreduktasy